Wave-packet propagation study of the charge-transfer dynamics of Rydberg atoms with metal surfaces - So, E; Bell, M; Softley, T (American Physical Society, 2009)
A wave-packet propagation study is presented of the ionization dynamics of xenon and hydrogen Rydberg atoms interacting with a metal surface in the presence of an external field. The calculations are performed using a Coulomb-wave discrete variable representation, which allows an efficient extension of previous calculations to a higher principal quantum number. The wave-packet calculations include nonadiabatic effects at avoided energy level crossings. Ionization probabilities as a function of distance from the surface are compared with complex-scaling calculations, which assume purely adiabatic traversal of the avoided crossings. A comparison is made between the dynamics calculated for the "normal" experimental situation, where the applied field is oriented so as to repel positive ions away from the surface, versus the dynamics for the reversed field situation, in which electrons are repelled from the surface. Overall it is clear that reversing the field direction has a pronounced effect on the ionization dynamics for any given starting level and that the nonadiabatic effects are most pronounced in the reversed field case. For certain field ranges, electron flux is found to be "backscattered" away from the surface in the reversed field configuration. Preliminary mean-field calculations are also presented to evaluate the effect of the acceleration of the atom on the ionization dynamics.